MACROECONOMIC POLICIES AND THEIR IMPACT ON THE AGRICULTURAL SECTOR AND ECONOMIC GROWTH IN SELECTED ARAB COUNTRIES FOR THE PERIOD 1990-2020 - Eman Alzubaidi; Walid Sultan Albajari (Mesopotamia Journal of Agriculture)
The research aims to study and measure the impact of macro policies (monetary and financial) on the agricultural sector and economic growth in some Arab countries, namely (Saudi Arabia and Jordan), with special reference to Iraq. The research relied on the descriptive approach with quantitative analysis using the statistical program (Eviews10). The research included a time series over a period of thirty-one years (1990-2020), where the co-integration mechanism and the error correction methodology (ECM) were used to find out the impact of some independent financial and monetary economic indicators on the variable value added of the agricultural sector of the sample countries, and then measure the value added of the agricultural sector. Estimated from the first model on the economic growth of the second stage v Using the two-stage method, in order to reach more accurate results, and one of the most important conclusions reached by the research is that all economic variables are stable at the first level and difference, so the ARDL autoregressive vector model was chosen to estimate the relationship between the long and short term variables. This model was used in order to know the nature of the relationship shown by the macro policies (financial and monetary) in the agricultural sector and the economic growth rates of all the sample countries, as it was found that the policies followed by the sample countries were ineffective. Which contributed to the low added value of the agricultural sector and thus reduced economic growth, especially in Iraq and Saudi Arabia as they are oil countries, while in Jordan the added value increased economic growth. The researcher recommended raising the efficiency of fiscal and monetary policies by relying on mechanisms that raise the agricultural added value, which in turn works to raise the economic growth rates of the sample countries.